CHARACTERISTICS, PHYSICAL ACTIVITIES AND NUTRITION INTAKE TOWARDS ELDERLY NUTRITIONAL STATUS IN TRESNA WERDHA PANTI - Ahmad Faridi; Via ningsih; Nur Setiawati Rahayu; Asri Werdhasari (Media Gizi Pangan, 2020)
Elderly (elderly) is a natural process that will surely be experienced by all those who are blessed with longevity. The anatomical structure or the process of aging is seen as deterioration in the cell. Based on SKRT morbidity data (2001) and Kor-Susenas (2001) data, there are 31.0% nutritional status of elderly people with low nutritional status, there is a normal nutritional status of 67.1%, while those with more nutritional status are 1.8 %. The success of development, among others, is marked by an increase in life expectancy that ultimately results in an increase in the number of elderly people (Ministry of Health, 2005 in Ratih et al, 2014). Factors that influence nutritional status in the elderly are characteristics, physical activity and nutrient intake. The purpose of the study was to identify the relationship of characteristics, physical activity and intake of nutritional substances with nutritional status in the elderly at the Tresna Werdha Budi Mulia 3 Social Institution in South Jakarta. This research method uses cross sectional. The sample is 147 people who are on Budi Mulia 3 PSTW using the Systematic Random sampling technique. Chi Square test shows that there is a significant relationship between energy intake (p = 0.040) and carbohydrate intake (p = 0.002) with the nutritional status of elderly in the Tresna Werdha Budi Mulia 3 Social Institution in South Jakarta. There was no significant relationship between protein intake, fat intake, characteristics (age, sex, marital status and level of education) and physical activity with the nutritional status of the elderly at the Tresna Werdha Budi Mulia 3 Social Institution in South Jakarta.